The Impact of Utilizing Uno Stacko on Arabic Learning Vocabulary Acquisition - Anggraeni, Ayu; Alfan, Muhammad; Rani, Noorazi (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This research addresses the apparent deficiency in Arabic vocabulary mastery among eighth-grade students at MTsN 7 Blitar, as revealed through the researchers' observations. The identified challenges stem from the limited strategies and media implemented in the teaching process. This study proposes incorporating the uno stacko game as an innovative solution to enhance Arabic vocabulary acquisition. The primary objectives of this research are to assess the impact of the uno stacko game on Arabic vocabulary mastery and to explore students' perceptions regarding the game. The research design adopts a quantitative pre-experimental approach, employing a one-group pretest-posttest design to evaluate the effectiveness of the uno stacko game. Data collection methods include observation, interviews, tests, questionnaires, and documentation. The collected data exhibit normal distribution, indicating the suitability of the data for statistical analysis. The analysis reveals a significant difference in the average scores between the pretest and posttest, with a notable increase of 0.55. This change falls within the moderate category, signifying a positive influence of the uno stacko game on Arabic vocabulary acquisition. The percentage change of 56.53% further supports this conclusion, indicating a substantial impact, and the study delves into students' perceptions of the uno stacko game. The average percentage of student perceptions is 99.1667%, reflecting an overwhelmingly positive response. This high percentage categorizes student perceptions as very good, suggesting a favorable view of the uno stacko game as an effective and engaging tool for learning Arabic vocabulary. The findings of this research highlight the positive influence of the uno stacko game on enhancing Arabic vocabulary mastery among eighth-grade students. Additionally, the overwhelmingly positive student perceptions emphasize the game's potential as a valuable educational resource. Recommendations for further research could involve more in-depth analysis of specific aspects of using the uno stacko game, exploring variations in learning strategies, and evaluating the long-term impact on Arabic vocabulary acquisition.